Second season syndrome. Issue 3 (6th June 2016) - Gandy, Rob
Abstract : How hard is it for a newly‐promoted football club to become established in the English Premier League? Rob Gandy explores the statistics of survival in top‐flight soccer Abstract : How hard is it for a newly‐promoted football club to become established in the English Premier League?Rob Gandy explores the statistics of survival in top‐flight soccer